Phytochemical characterization, total phenolic and flavonoid content, antioxidant capacity, enzymatic profiling, and cytotoxicity of Bidens pilosa and Croton sp. from Colombia for applications in skin health - Patricia Quintero-Rincón; Karina Caballero-Gallardo; Elkin Galeano; Oscar Flórez-Acosta (PLoS ONE, 2026)
This study investigated the chemical and biological potential of Bidens pilosa and Croton sp., plants from megadiverse ecosystems in Colombia, collected in Santander de Quilichao (Cauca) and San Basilio de Palenque (Bolivar). The chemical profile was analyzed by UHPLC-ESI-Orbitrap-HRMS, and the total phenolic and flavonoid content was quantified using colorimetric methods. Antioxidant capacity was assessed using methods that evaluate reducing power and electron transfer mechanisms. The inhibition of key enzymes in skin aging, such as tyrosinase, hyaluronidase, and collagenase, was evaluated, as well as cytotoxicity in keratinocytes and human melanoma cells. Chemical characterization revealed distinctive phytochemical profiles: B. pilosa contained 21.1 mg GAE/g DT of phenolics and 64.6 mg RE/g DT of flavonoids, dominated by p -coumaric acid and rosmarinic acid, while Croton sp. exhibited higher levels of phenolics (169.4 mg GAE/g DT) and 54.1 mg RE/g DT of flavonoids, highlighting rosmarinic acid, p -coumaric acid and quercetin. Both extracts showed significant antioxidant capacity and enzyme modulation, including moderate collagenase inhibition (53.9–55.0%), high hyaluronidase inhibition (64.5–76.5%), and low tyrosinase inhibition (11.1–12.7%), suggesting protection of extracellular matrix and hyaluronic acid during skin aging. Sun protection factor was limited (SPF: 14.5 for B. pilosa and 11.6 for Croton sp.), with low ultraviolet absorption, consistent with low antityrosinase activity. Cytotoxicity assays demonstrated that B. pilosa was not toxic to HaCaT keratinocytes (IC₅₀ > 500 µg/mL) and displayed antimelanoma activity on A375 cells (IC₅₀ = 398.6 µg/mL), whereas Croton sp. showed moderate selectivity towards melanoma cells (IC₅₀ HaCaT = 329.5 µg/mL; IC₅₀ A375 = 189.0 µg/mL). The results suggest that both plants have potential in dermatological applications such as anti-melanoma agents, antioxidants, and modulators of skin aging enzymes, although highlight the importance of improving strategies to maximize their efficacy and safety.